PENGARUH PROMOSI JABATAN TERHADAP PRESTASI KERJA KARYAWAN PADA PT.SINARMAS MULTIFINANCE PALEMBANG - Muhammad Imam Tohari; Muhammad Ridwan (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
Promotion is a means to encourage employees to be better or more eager to do a job in a corporate environment. By looking at these facts, the employee performance that leads to promotion must be done effectively in order to be accepted by all parties without anyone feels aggrieved. Promotions and employees' performance very closely and is also important within the company. This study discusses in depth about the influence of scientific and Campaign Against Occupation Employee Achievement In PT.Sinarmas Multifinance Palembang. The purpose of this study is to determine the effect of promotion on employee performance on PT.Sinarmas Multifinance Palembang.The results of this study are as follows: (1) There is a positive influence between promotion on employee performance on PT.Sinarmas Multifinance Palembang, (2) large or strong influence of promotion on employee performance on PT.Sinarmas Multifinance Palembang is by 75,9% , while 24,1% is influenced by other factors.Applications of this research in the future to make the boss always gives high motivation of the employees PT.Sinarmas Multifinance Palembang. Keywords :Promotions, job title, employee performance.